Evaluating the Effect of Organizational Relationship on Employee Satisfaction and Firm Growth: Focus On Negeri Sembilan - Iqwo, Tawo Eyang (2012)
This paper attempts to assess the correlations between organizational relationships and employee satisfaction as well as its subsequent impact on organizational growth, with focus on Negeri Sembilan while using variable such as general satisfaction, employee relationship, remunerations, benefits and organizational culture, employee loyalty to measure employee satisfaction and commitment, employer relationship, trust, shared values and goals and respect to measure organizational relationship. Data was collected from 150 employees in Negeri Sembilan. Correlation and multiple regression were used to analyze the data. Based on the analysis, there is a positive relationship between organizational relationship and employee satisfaction as well as organizational relationship and employee satisfaction as well as organizational growth, with constructs of shared values and goals and commitment having the most significant influence on organizational relationship and general satisfaction and remuneration, benefits and organizational culture were seen to have the most impact on employee satisfaction. This suggests the most important influencers of organizational relationship and employee satisfaction respectively. Finally the results prove that a positive organizational relationship influence employee satisfaction as well as organizational growth.